Chinese Youths’ Physical Activity and Flourishing During COVID-19: The Mediating Role of Meaning in Life and Self-Efficacy - Zhou, Jun; Huo, Yongquan (Frontiers in Psychology, 2022)
Physical activity has wide-ranging consequences for people's physical, mental and social health. Although its beneficial effects on well-being were widely studied, how physical activity promotes well-being remained unclear. The present study utilized the measure of PARS-3, FS, C-MLQ and GSES to examine the connection between physical activity and flourishing and the multiple mediation effects of meaning and self-efficacy with 827 Chinese undergraduates. The results indicated that (a) physical activity positively predicted flourishing; (b) meaning in life and self-efficacy played mediating roles in physical activity and flourishing, separately and jointly. Our findings revealed the mechanism of physical activity fostering flourishing, providing an empirical basis for promoting health and flourishing, especially during COVID-19.